(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
Small businesses and private enterprises play a crucial role in the global economy, contributing significantly to innovation, job creation, and economic growth. However, these entities often face various challenges that threaten their stability and sustainability. This article explores measures aimed at ensuring stability in small businesses and private enterprises. Through a comprehensive review of literature and empirical evidence, we identify key strategies such as financial management, strategic planning, innovation, human resource development, and regulatory compliance. Implementing these measures can help mitigate risks, enhance resilience, and foster long-term success for small businesses and private enterprises